(untitled) (Confluenţe Bibliologice, 2026)
Artiﬁcial intelligence (AI) is redeﬁning the functions of the contemporary library, oﬀering new perspectives on how information, research, and user interaction services are delivered. This article examines the applicability of AI in key areas of library activity— from metadata processing, bibliographic work, and reference services to digital collection management and research support. It presents implementation examples from various libraries, along with speciﬁc AI tools that contribute to the eﬃciency of professional tasks. The study highlights the transformative potential of AI and its relevance in strengthening the library’s role within an evolving academic and informational ecosystem.